Comportamento reológico de blendas poliméricas de poli(metacrilato de metila) e polímeros estirênicos - Reinaldo, Juciklécia da Silva (2017)
The aim of this work was to investigate the influence of the effect of the chemical structure on the rheological behavior in the linear viscoelastic region of polymer blends consisting of acrylic polymers (poly (methyl methacrylate) homopolymer (PMMAh), poly (methyl methacrylate) with elastomeric particles (PMMAe)) and styrenic polymers (polystyrene (PS), styrene-acrylonitrile copolymer (SAN), acrylonitrile-butadiene-styrene copolymer (ABS) and methyl methacrylate-butadiene-styrene copolymer (MBS)). Fourier transform infrared spectroscopy (FTIR) showed a different bands characteristic of the chemical structures and tje differential scanning calorimetry (DSC) identified the glass transition temperatures (Tg) related to acrylics, styrenics and elastomeric phases of PMMAe, ABS and MBS. The results of the chemical compositions of the SAN and ABS showed that the percentage of AN were within the miscibility window for mixtures with PMMA, ie 25 and 21 wt%, respectively. The rheological results obtained at low frequency in the region of linear viscoelasticity showed that there was a significant change in the rheological behavior in relation to the use of PMMAh when compared to the use of PMMAe and also showed the miscibility and immiscibility of the polymer blends with structural variation of the minority components. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed the immiscibility in polymer blends with PS and miscibility in PMMAh/SAN blend, as well as the miscibility between PMMAh and free SAN of the ABS in the PMMAh/ABS blend, corroborating with the rheological results. However, the polymer blends with PMMAe presented complex microrreological results due to the presence of the elastomeric phase. Photomicrographs showed the miscibility between PMMA and SAN in the PMMAe/SAN and PMMAe/ABS blends, where PMMAe presented core-shell particles and ABS showed dispersed phase domains of the polybutadiene.